An investigation into how grade 10 learners make meaning during the teaching and learning of the topic on nutrition in Life Science: a case study - Mwiikeni, Helena Twiihaleni,Shimwafeni-Mwiikeni, Helena Twiihaleni (Rhodes University, Faculty of Education, Department of Education, 2013)
The integration of learners' prior everyday knowledge and experiences during teaching and learning is a pre-requisite in the Namibian curriculum. The curriculum states that if learners are taught in a way which builds on what they already know and they relate new knowledge to the reality around them, their learning in school can be made more meaningful. Thus, learners' meaning making in the topic on nutrition was researched to find out whether elicitation and integration of learners' prior everyday knowledge and experience in the nutrition topic enhanced or constrained their learning. This study was conducted with my grade10 learners at the school where I am currently teaching. The school is located in a rural area in Oshana region in Northern Namibia. This study is situated within an interpretive paradigm. Within the interpretive paradigm a qualitative case study approach was adopted. I considered this methodological orientation appropriate in this study as it allowed me to use the following methods: document analysis, brainstorming and discussion, semi-structured interviews and a focus group interview, practical activities with worksheets and observation and reflection. Multiple methods to gather data were used for triangulation and validation purposes. For data analysis purposes, the data sets were colour coded to derive themes and analytical statements. Ethical consideration was also taken seriously in this study. The findings from this study revealed that integration of learners' prior everyday knowledge and experience enabled learners to understand science better particularly in the topic of nutrition. The study also revealed that learners possess a lot of prior everyday knowledge and experience about food they eat in their homes. However, data from the community members revealed that there are some contradictions between learners' prior everyday knowledge and the science content of the topic. Nonetheless, engaging learners in practical activities in the testing of food (local and conventional western type foods) helped them to make meaning of the content learned. I therefore, recommend that learners' prior everyday knowledge and experiences should be incorporated during teaching and learning of the topic on nutrition. The study also recommends that the Department of Education should ensure that teachers get the necessary support and training on how to integrate learners' prior everyday knowledge and experiences.
Keywords: Nutrition -- Study and teaching (Secondary) -- Namibia -- Oshana -- Case studies; Environmental sciences -- Study and teaching (Secondary) -- Namibia -- Oshana -- Case studies; Experiential learning -- Namibia -- Oshana -- Case studies; Education, Secondary -- Namibia -- Oshana